The Psychological Impact of a Flu-like Outbreak on a Post-COVID-19 Community: A Case Study in Magwegwe Suburbs in Bulawayo Metropolitan Province, Zimbabwe - Khumbulani Siziba (Utan Kayu Publishing, 2025)
AbstractThis qualitative case study explored the psychological impact of a flu-like outbreak on a community in Magwegwe Suburbs, Bulawayo Province, Zimbabwe that had previously experienced the COVID-19 pandemic. The study aimed to: 1) examine the community's levels of trauma, resilience and mental health outcomes; 2) investigate the psychosocial effects of health-related anxiety and stigma; and 3) evaluate the utilization of mental health services before, during and after the outbreak. Data was collected through in-depth interviews, focus groups, open-ended Questionnaire and analysis of medical records. The findings indicated that the community exhibited elevated rates of PTSD, depression and health-related anxiety, alongside both community cohesion and interpersonal conflicts. Significant barriers to accessing mental healthcare were also identified. The study provided crucial insights into the long-term psychological toll of compounding public health crises in a low-resource setting. The results informed recommendations for comprehensive, community-based mental health programmes, integrated primary care-based services and continued research engagement with affected populations. Overall, the findings highlight the need for tailored interventions to support community resilience in the face of successive public health emergencies.